From equity talk to equity walk : expanding practitioner knowledge for racial justice in higher education - McNair, Tia Brown, 1952-; Bensimon, Estela Mara; Malcom-Piqueux, Lindsey E., 1980-; Association of American Colleges and Universities; Jossey-Bass Inc. (Hoboken, NJ : Jossey-Bass, a Wiley Brand, 2020)
"AAC&U launched its Making Excellence Inclusive (MEI) initiative in 2002 as a framework with four primary objectives: a focus on student intellectual and social development, a purposeful development and utilization of organizational resources to enhance student learning, a call for attention to the cultural difference learners bring to educational experiences, and a welcoming community that engages all of its diversity in the service of student and organizational learning. More recently, postsecondary educators have started to ask more critical and practical questions related to education equity and engaged learning pedagogies. The new emphasis on equity addresses the changing realities and increasing demands on higher education for accountability and completion goals. Sponsorship: AAC&U will help promote, resell, and launch the book at its annual conference. Hot Topic: Making Excellence Inclusive (MEI) is AAC&U's guiding principle for access, student success, and high-quality learning. MEI is designed to assist colleges integrate diversity, equity, and educational efforts into their institutional operations. Active Authors: Authors hold a conference session at AAC&U's annual meeting that approximately 2,000 higher education leaders attend. This is one strategy for promotion along with the email blasts to AAC&U's network of 65,000 educators and ads in their personal periodicals (Diversity & Democracy, Peer Review, and Liberal Education)"--
From equity talk to equity walk -- Building an equity-minded campus culture -- Using and communicating data as a tool to advance equity -- Aligning strategic priorities and building institutional capacity -- Building capacity for equity-mindedness among first-generation equity practitioners.
Includes bibliographical references and index.
Keywords: Educational equalization -- United States; Minorities -- Education -- Social aspects -- United States; Education -- Aims and objectives; Teachers -- Training of -- United States; Education -- Aims and objectives; Educational equalization; Minorities -- Education -- Social aspects; Teachers -- Training of; United States